Comparative Aroma Profile Analysis and Development of a Sensory Aroma Lexicon of Seven Different Varieties of Flammulina velutipes - Wang, Ruijuan; Zhang, Yueyan; Lu, Huan; Liu, Jianyu; Song, Chunyan; Xu, Zhen; Yang, Hui; Shang, Xiaodong; Feng, Tao (Frontiers in Nutrition, 2022)
Flammulina Velutipes (F. velutipes) is widely planted all over the world and is rich in nutrients. However, the research on the flavor of F. velutipes is relatively rare, which limits its application in deep processing. The objectives of this research were (1) to study the relationship between sensory analysis and aroma-active compounds of F. velutipes varieties, and (2) to develop a lexicon of F. velutipes, and (3) according to different aroma characteristics, F. velutipes' deep processing is expected. Flavor of 7 species of F. velutipes were described and evaluated by sensory evaluation experiment. The volatile compounds in seven kinds of F. velutipes were detected by headspace solid phase microextraction combined with gas chromatography-mass spectrometry (GC-MS). A total of 74 volatile compounds were found, including 23 alcohols, 5 aldehydes, 2 phenols, 1 acid, 16 esters, 7 ketones, 1 ether, 13 hydrocarbons, 1 sulfide, 1 acyl compound and 4 heterocyclic compounds. And it was found that there was a high correlation of sensory evaluation results and compound content between sample No.61490, 61486 and 61530, and a high correlation between sample No.61525 and sample No.61523. A lexicon for describing flavor attributes of F. velutipes was developed and they could be grouped in categories such as fruity (apple, banana, cucumber, citrus and berry), alcoholic (whisky, fermented fruit), milky (creamy), floral (hyacinth, phoenix, iris and mint), sulfurous (onion) and musty (mud). This research will provide a theoretical basis for the future study of F. velutipes flavor and the development and application of F. velutipes products.